Pendampingan Fatayat-Muslimat Desa Mlaran dalam upaya Menumbuhkan Toleransi Beragama Berbasis Qur'anic Empowerment - Nur Hikmah; Lina Riyani; Nevlin Marella Cahari; Muhammad Fahri Musthofa; Muhammad Manarul Huda; Salis Irvan Fuadi (Svarga Pena : Jurnal Pengabdian Kepada Masyarakat, 2025)
Religious tolerance is a fundamental element in maintaining social harmony within pluralistic societies. However, at the local community level, the understanding and practice of tolerance often remain normative and insufficiently internalized. This community service program aims to foster religious tolerance through mentoring the Fatayat–Muslimat community of Mlaran Village based on Qur’anic Empowerment. The method employed is a community organizing approach using Participatory Action Research (PAR), which actively involves the assisted community in the stages of planning, implementation, reflection, and evaluation. The activities include social mapping, Qur’anic empowerment studies, reflective group discussions, and capacity building for women as agents of tolerance. The results indicate an improvement in participants’ understanding and attitudes toward religious tolerance, more inclusive social behavior, the emergence of new social institutions in the form of women’s discussion forums, and the development of local female leaders who actively promote tolerance within the community. These findings demonstrate that a Qur’anic empowerment–based women’s empowerment approach is effective in encouraging social transformation and strengthening religious moderation at the grassroots level.